Drivers of semiconductor production allocation - Zadorozhnaia, Kristina (2025)
This thesis explores the global distribution of semiconductor production to identify the key factors driving the dominance of main countries in this essential industry. It highlights the way in which semiconductors have become central to modern technology and economic influence, and their production is concentrated in the US, Taiwan, South Korea and several other regions. Through quantitative analyses of industry data, policy documents and historical examples, the study highlights two major forces driving market leadership: effective industrial policy and path dependence. Although enabling factors such as skilled labour, innovation capacity, investment and niche specialisation sustain competitive advantage, it is long-term strategic policies and historical backgrounds that have consolidated the national lead. The insights gained from the study provide an understanding of how geopolitical, institutional and economic factors have shaped the concentrated but interdependent global semiconductor landscape.